2017
DOI: 10.1007/s40261-017-0577-1
|View full text |Cite
|
Sign up to set email alerts
|

Acetazolamide as Add-on Diuretic Therapy in Exacerbations of Chronic Heart Failure: a Pilot Study

Abstract: BackgroundCongestion is the main cause of morbidity in patients with heart failure. Treatment of fluid overload is often challenging in everyday clinical practice.ObjectiveThe aim of this study was to determine the diuretic effect of acetazolamide in patients with exacerbations of chronic heart failure, in addition to their stable diuretic therapy.MethodsThis was a single-center, unblinded study. Patients hospitalized with chronic heart failure exacerbations, with left ventricular ejection fraction (EF) < 50% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 12 publications
2
36
0
1
Order By: Relevance
“…Acetazolamide has been tested in other small prospective studies in AHF. A recent open‐label study randomised 20 AHF patients with ejection fraction < 50% and clinical signs of volume overload to acetazolamide or nothing in addition to usual care . Diuresis, natriuresis, net fluid balance and subjective improvement of dyspnoea were significantly greater in patients receiving acetazolamide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acetazolamide has been tested in other small prospective studies in AHF. A recent open‐label study randomised 20 AHF patients with ejection fraction < 50% and clinical signs of volume overload to acetazolamide or nothing in addition to usual care . Diuresis, natriuresis, net fluid balance and subjective improvement of dyspnoea were significantly greater in patients receiving acetazolamide.…”
Section: Discussionmentioning
confidence: 99%
“…However, an observational study in AHF has found that the addition of acetazolamide improves loop diuretic efficiency with approximately 100 mmol sodium excreted in surplus for every 40 mg furosemide‐equivalent dose administered . Other small studies, often before the era of evidence‐based heart failure treatment, corroborate these findings and make acetazolamide an interesting agent to study in combination with loop diuretics for prevention or treatment of diuretic resistance . Acetazolamide blocks sodium bicarbonate reabsorption in the renal proximal tubules, offering more sodium to Henle's loop, hence boosting the effect of loop diuretics, which might be especially useful in states of poor renal blood flow .…”
Section: Introductionmentioning
confidence: 98%
“…However, the experience in daily clinical practice is limited . Verbrugge et al., in a cohort of 54 patients with acute HF and volume overload, found that a combined therapy with acetazolamide was an independent predictor of natriuresis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the addition of acetazolamide improved loop diuretic efficacy with approximately 100 mg of sodium excretion per 40 mg of furosemide equivalent dose . In other more recent randomized open‐label study that enrolled 20 patients with acute HF and signs of volume overload, the addition of acetazolamide over standard diuretic therapy resulted in some additional effects in parameters of diuretic efficacy and relief of dyspnea …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation